Growth and Yield Response of Okra (Abelmoschus esculenthus L. Moench) with Bio-slurry of cow - Fitria Febrina; Lisa Mawarni; Chairani Hanum (Universitas Sumatera Utara, 2019)
Okra has potential to be horticulture development because it has a high economic value. One of alternative to cultivate vegetable crop is using organic fertilizer. The organic fertilizer that can be used in okra cultivation is Bio-slurry of cow. Bio-slurry is organic fertilizer made from cow feces and water. The process of making this bio-slurry fertilizer through anaerobic in closed room. This organic fertilizer is able to neutralize acid soil and increase humus approximately 10-12%. The purpose of this study was to determine the dose of Bio-slurry on growth and yield of okra. This study was conducted at Tuntungan district on May to August 2017. This research used non-factorial randomized block design with five doses of Bio-slurry treatment: 0, 10, 20, 30 and 40 ton/ha. The results showed that Bio-slurry treatment not significant effect on stem diameter, shoot dry weight and root shoot ratio. Bio-slurry treatment increase the fruit length.